2004
DOI: 10.1590/s0034-89102004000700006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the length and timing of nighttime naps on task performance and physiological function

Abstract: ObjectiveTo examine the effects of the length and timing of nighttime naps on performance and physiological functions, an experimental study was carried out under simulated night shift schedules. Methods Six students were recruited for this study that was composed of 5 experiments. Each experiment involved 3 consecutive days with one night shift (22:00-8:00) followed by daytime sleep and night sleep. The experiments had 5 conditions in which the length and timing of naps were manipulated: 0:00-1:00 (E60), 0:00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
0
21
0
2
Order By: Relevance
“…However, findings related to the duration and severity of sleep inertia and the relationship of sleep inertia to both nap length and timing remain controversial and are based on modest sample sizes. [59][60][61] Symptoms of sleep inertia measured as sleepiness, fatigue, and dullness have been reported to increase in the first hour immediately after a night-shift nap with subsequent decreases in reported symptoms over time to prenap levels. 59 Impairments in cognitive performance upon awakening even after a full night's sleep are not consistent, with severe impairment ranging from the first 3 minutes of awakening 61 to up to 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings related to the duration and severity of sleep inertia and the relationship of sleep inertia to both nap length and timing remain controversial and are based on modest sample sizes. [59][60][61] Symptoms of sleep inertia measured as sleepiness, fatigue, and dullness have been reported to increase in the first hour immediately after a night-shift nap with subsequent decreases in reported symptoms over time to prenap levels. 59 Impairments in cognitive performance upon awakening even after a full night's sleep are not consistent, with severe impairment ranging from the first 3 minutes of awakening 61 to up to 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of timing, naps taken earlier in the night shift (between midnight and 2 AM) have greater performance and physiological benefit than do naps taken later in the night (4 AM-6 AM). 60 Lewis reviewed the literature in this area (16 studies with a high level of evidence) and found that the evidence suggests that a 40-to 60-minute nap between 2 AM and 4 AM was superior to a longer nap (>60 minutes) earlier in the shift. 63 This evidence poses an organizational challenge for health care, where coverage is required throughout the shift period.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, o cochilo noturno pode ter um efeito negativo sobre a atuação dos trabalhadores, uma vez que, ao acordar, a pessoa pode ser afetada pela "inércia do sono", caracterizada pela falta de disposição ao despertar, que pode durar de três minutos até duas horas, que causaria mais danos do que benefícios ao desempenho (15) . Canopus faz uso do artifício do cochilo e refere que "o meu horário de sono, que é sagrado, é das 4:00 as 6:00".…”
Section: De Madrugada Eu Fico Muito Cansada Lá Pelas Três Horas Da Munclassified
“…Recently, we also examined the effects of 5 different nap conditions during night duty regarding nap length and timing under laboratory conditions 32) . In short, the effects of naps taken at 0:00 for 60 and 120 min, naps taken at 4:00 for 60 and 120 min, and no-nap conditions on alertness and performances were investigated.…”
Section: Effective Length and Timing Of The Nighttime Napmentioning
confidence: 99%